A Summary: Portraying the Legal Culture and the European Human Rights Culture of the European Court of Human Rights and the European Court of Justice through Interviews - Nina-Louisa Arold Lorenz (Rechtsgeschichte - Legal History, 2021)
To show the impact of interviews for European legal studies, this article summarizes the earlier findings of two books, the first by Arold on the legal culture of the European Court of Human Rights (ECtHR), and the second by Arold Lorenz, Groussot and Petursson on the legal culture of the European Court of Justice (CJEU) and European human rights culture. In doing so, this article draws a portrait of the legal cultures of the two European courts and explains how (and to what extent) differences between European legal cultures brought to the benches of the two courts by their judges (plus for the CJEU: advocates general) impact cases concerning human rights. This article highlights parts of the methodology employed, i. e. a combination of interviews and case law analysis. The results show that there is no clash of a multitude of individual (legal) cultures at the courts; instead, both have established their own legal cultures that unite their members. Importantly, the legal cultures of the ECtHR and CJEU show some distinctive differences, which are relevant when assessing European human rights culture. Studying European human rights culture, in turn, is key for an assessment of the recent attempt to merge the two systems through the accession of the European Union to the European Convention on Human Rights (ECHR).